The viability of employment bond clauses in retaining entry-level employees of BPO companies - Lim, Zervin Gaitla (Animo Repository, 2015)
The number of college graduates who are having a difficult time finding jobs is increasing annually. On the other hand, companies are continually confronted with problems such as high employee turnover rates, and high costs of hiring and training employees; this is especially true in highly competitive and rapidly growing industries, such as the Business Process Outsourcing (BPO). To mitigate the impact of such problems, companies resort to various methods to ensure that their entry-level employees stay in the company for a significant period. The most popular method employed by BPO companies is by including an employment bond clause in their entry-level employees’ contract. An employment bond clause is a covenant in the employment contract which prohibits the employee from leaving the company within a certain period, and obligates the employee to pay a certain sum in order for them to validly leave the company. This research study analyzed the viability of the employment bond clause as a device in retaining entry-level employees of BPO companies. This was done by examining the employment bond clause’s legality, its effectiveness in retaining employees, and its effect on the employees’ job involvement and organizational commitment. In determining its legality, a case analysis was done using the author’s own employment contract with a previous employer, together with the pertinent laws, rules, and jurisprudence on the subject. On the other hand, the employment bond clause’s effectiveness in retaining employees was tested by conducting a survey with 95 employees of two (2) BPO companies. In the survey, the employees were asked to rate how effective they perceived the employment bond clause is in making employees stay in their companies. In addition, the employees were also asked to rate the effectiveness of other employment factors, such as career development program, compensation and benefits package, organizational culture, and nature of work, in retaining employees. In the same survey, the employees were further asked to specify the effect that the employment bond clause has on their job involvement and organizational commitment. The conclusion reached is that the employment bond clause is an illegal contract and therefore has no binding force and effect. Moreover, the survey results have indicated that most employees observed the employment bond clause as ineffective, and substantially inferior to the other employment factors earlier mentioned in making employees stay. Lastly, the survey results have also shown that more than a majority of the employees perceived the employment bond clause to have a negative effect in both their job involvement and organizational commitment which does not benefit the company in the long run. Based on such findings, it is recommended that BPO companies should stop the use of the employment bond clause. The researcher suggests though that BPO companies consider the other employment factors, which the employees found to be more effective in making them stay, to help them in maximizing their investment.